Some approaches to the definition of the notion «future family doctor’s professional self-improvement» - Остраус, Юлія (Pedagogy of Higher and Secondary Education, 2014)
Ostraus Y. M. Some approaches to the definition of the notion «future family doctor’s professional self-improvement». The author analyses the pedagogical approaches to the definition of the terms «self-improvement» and «professional self-improvement». The meaning of the notion «future family doctor’s professional self-improvement» is defined.